2014
DOI: 10.1155/2014/905903
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Silicon Carbide Thin Films Prepared with High Deposition Rate by Hot Wire Chemical Vapor Deposition Method

Abstract: Structural, optical, and electrical properties of hydrogenated silicon carbide (SiC:H) films, deposited from silane (SiH4) and methane (CH4) gas mixture by HW-CVD method, were investigated. Film properties are carefully and systematically studied as function of deposition pressure which is varied between 200 mTorr and 500 mTorr. The deposition rate is found to be reasonably high (9.4 nm/s<rd<15.54 nm/s). Formation of SiC:H films is confirmed by FTIR, Raman, and XPS analysis. XRD and Raman analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…It is seen that the bandgap decreases with pyrolysis temperature, with a sudden change between 1100°C and 1200°C. Studies on a ‐SiC thin films synthesized by vapor deposition revealed that the bandgap of this type of material can be drastically affected by Si:C ratio and hydrogen concentration: increasing carbon concentration leads to an increase in the bandgap; and hydrogen can also widen the bandgap . Previous study on the network structure of this a ‐SiC revealed that the material does contain a small amount of extra carbon more than the necessary to form stoichiometric SiC within the Si‐containing phase.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is seen that the bandgap decreases with pyrolysis temperature, with a sudden change between 1100°C and 1200°C. Studies on a ‐SiC thin films synthesized by vapor deposition revealed that the bandgap of this type of material can be drastically affected by Si:C ratio and hydrogen concentration: increasing carbon concentration leads to an increase in the bandgap; and hydrogen can also widen the bandgap . Previous study on the network structure of this a ‐SiC revealed that the material does contain a small amount of extra carbon more than the necessary to form stoichiometric SiC within the Si‐containing phase.…”
Section: Discussionmentioning
confidence: 91%
“…Studies on a-SiC thin films synthesized by vapor deposition revealed that the bandgap of this type of material can be drastically affected by Si:C ratio and hydrogen concentration: increasing carbon concentration leads to an increase in the bandgap; 28,36,37 and hydrogen can also widen the bandgap. 38,39 Previous study 24 on the network structure of this a-SiC revealed that the material does contain a small amount of extra carbon more than the necessary to form stoichiometric SiC within the Si-containing phase. However, the concentration of the carbon and the composition of the samples remained the constant within the testing temperature range, 24 indicating the bandgap change was not from the decrease in the carbon concentration.…”
Section: Discussionmentioning
confidence: 94%
“…The silicon dioxide and suboxides, including Si 2 O, SiO, Si 2 O 3 and SiO 2 , correspond to +1, +2, +3, and +4 oxidation states, respectively. In addition, the a-Si x C y :H interlayer also exhibits the Si-C peak with a binding energy of ∼100.3 eV, as shown in figure 4(d), which means that the carbon dopant can be bound to the silicon core atoms [34]. In the a-Si:N interlayer, the nitrogen dopant atoms are not bonded to the silicon atoms but are located between the silicon structures, which is consistent with the XPS spectra of the N1s peak, as shown in the inset of figure 4(b).…”
Section: Structural Analysis Of the Silicon-based Interlayermentioning
confidence: 96%
“…[58][59][60] The peaks at 530.2 and 532.5 eV in the SiC supported catalyst are attributed to the low-coordinated and high coordinated O-Si, respectively, while the peak located at 531.6 eV belongs to the O-Si-C bond. [61][62][63] It was found that the main type of functional group for the Cu1:Ce3/CNT and Cu1:Ce3/AC catalysts was OQC-O. Existence of abundant surface oxygen groups in AC leads to the decreased hydrophobicity of carbon, ion-exchange capability, and electronic properties.…”
Section: Resultsmentioning
confidence: 99%